Assessment of individual shedder status and background DNA on objects: Direct or indirect transfer?. Issue 1 (December 2019) - Rolo, M.; Sampaio, L.; Balsa, F.; Bento, A.M.; Gouveia, N.; Serra, A.; Brito, P.; Lopes, V.; São-Bento, M.; Bogas, V.; Cunha, P.; Porto, M.J.; et al.
Abstract: Improvements in scientific techniques allowed the analysis of limited amounts of DNA and the testing of not only body fluids but also touch DNA. The possibility of DNA transfer often raises the question of how the DNA was deposited: directly or by indirect transfer? Therefore, it is important to comprehend the factors that can influence it. Our study shows that background DNA and DNA indirect transfer are in fact a reality, having the potential to interfere with target DNA detections, and corroborates that area of contact and type of material are of importance on DNA transfer.